2009
DOI: 10.1055/s-2008-1039109
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pleural Effusion: Who Benefits from a Tunneled Pleural Catheter?

Abstract: Recurrent malignant pleural effusion (MPE) is a common concomitant phenomenon of malignant disease, which can worsen the patient's quality of life and lead to significant morbidity. Tunneled indwelling pleural catheters (TIPC) offer new modalities in patients with recurrent MPE and impaired dilatability of the lung. We report on our experience with 100 consecutive patients suffering from recurrent benign (n = 12) and malignant pleural effusion (n = 88) who were treated with TIPC. The catheter was placed during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Schneider et al [5] reported a complication rate of 9% in the total 100 patients with malignant and benign effusions treated with PleurX catheter. In this study, the authors did not specify whether the complications occurred in patients with benign or malignant effusions.…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schneider et al [5] reported a complication rate of 9% in the total 100 patients with malignant and benign effusions treated with PleurX catheter. In this study, the authors did not specify whether the complications occurred in patients with benign or malignant effusions.…”
Section: Complicationsmentioning
confidence: 99%
“…A recurrent effusion is usually defined as repetitive fluid accumulation despite optimal medical management of the underlying condition. Those effusions are usually treated with multiple therapeutic thoracenteses prior to considering other options [5,6].…”
Section: P Leural Effusion (Pe) Is Simply Defined As Excess Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Trapped lung unsurprisingly led to a higher chance of persistent output. Nonetheless, it has been observed that patients with IPC inserted for trapped lung can still achieve SP, 12,15,17,18,20 or their lung expansion will improve after IPC. 17 In our cohort, two patients had their trapped lung reexpanded after IPC insertion; one of whom had IPC removed successfully without re-accumulation of effusion.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled rate of SP in MPE patients has been reported to be 45.6%, 11 achieved after a mean duration of 26 to 56 days after IPC insertion. [11][12][13][14][15][16][17][18][19][20] The possibility of SP is attractive as there is a chance that an IPC will no longer be required. The aims of this study were to review our single-centre experience of the safety of IPC in the management of symptomatic MPE and to explore the potential clinical factors associated with SP.…”
Section: 持續胸腔引流治理惡性胸腔積液:與自發性胸膜 固定相關的因素mentioning
confidence: 99%